2015
DOI: 10.1097/ta.0000000000000630
|View full text |Cite
|
Sign up to set email alerts
|

Fresh frozen plasma and spray-dried plasma mitigate pulmonary vascular permeability and inflammation in hemorrhagic shock

Abstract: Both FFP and SDP similarly modulate pulmonary vascular integrity, permeability, and inflammation in vitro and in vivo in a murine model of HS and trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 36 publications
5
74
0
Order By: Relevance
“…Nanoparticles tend to distribute to organs with high vascular permeability, and even though the lung vasculature is not usually permeable, vascular permeability increases during hemorrhage. 20 In summary, we have developed a TF-targeted nanofiber that specifically binds to the site of hemorrhage and reduces blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles tend to distribute to organs with high vascular permeability, and even though the lung vasculature is not usually permeable, vascular permeability increases during hemorrhage. 20 In summary, we have developed a TF-targeted nanofiber that specifically binds to the site of hemorrhage and reduces blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other studies in animal hemorrhage models where plasma repaired the pulmonary endothelial injury induced by hemorrhagic shock. 8,9,10 A retrospective study by Peiniger et al analyzed 1,250 massively transfused trauma patients with and without TBI and found that a high plasma:RBC transfusion ratio of >1:2 was an independent predictor of decreased mortality (OR 0.48, 95% CI 0.29 – 0.81) in patients with TBI. 21 However, another retrospective study by Spinella et al examined 850 massively transfused patients and found that a high plasma:RBC transfusion ratio was associated with increased survival in non-TBI patients, while a high platelet:RBC ratio was associated with survival in TBI patients.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,7 This effect may be due to plasma’s ability to repair endothelial injury and reduce vascular permeability, which has been demonstrated in vitro and in animal models of hemorrhagic shock. 8,9,10 In a large animal model of combined TBI and hemorrhagic shock, plasma-based resuscitation reduced secondary brain injury 11 and improved neurologic recovery. 12 This benefit was attributed to improved cerebral perfusion, mitigation of glutamine-mediated excitotoxicity, and reduced mitochondrial dysfunction with plasma resuscitation.…”
Section: Introductionmentioning
confidence: 99%
“…Liberal resuscitation with crystalloids and artificial colloids increases hydrostatic pressure without repairing the endothelial injury, resulting in edema and the edema-related complications which were common in the pre-DCR era (Figure 1). In contrast, in vitro 72,73,74 and animal models 75,76 of hemorrhagic shock demonstrate that plasma restores microvascular integrity, in part by repair of the endothelial glycocalyx layer (EGL). In a large animal model of concomitant hemorrhagic shock and TBI, resuscitation with FFP resulted in less secondary brain injury compared to resuscitation with crystalloid or artificial colloid, likely secondary to restoration of cerebral endothelium.…”
Section: Pharmacologic Treatment Optionsmentioning
confidence: 98%